Research versus practice: The dilemmas of research ethics in the era of learning health‐care systems. (18th March 2019) - Piasecki, Jan; Dranseika, Vilius
Abstract: In this article we attempt to answer the question of how the ethical and conceptual framework (ECF) for a learning health‐care system (LHS) affects some of the main controversies in research ethics by addressing five key problems of research ethics: (a) What is the difference between practice and research? (b) What is the relationship between research ethics and clinical ethics? (c) What is the ethical relevance of the principle of clinical equipoise? (d) Does participation in research require a higher standard of informed consent than the practice of medicine? and (e) What ethical principle should take precedence in medicine? These questions allow us to construct two opposite idealized positions on the distinction between research and practice: the integration model and the segregation model of research and practice. We then compare the ECF for an LHS with these two idealized positions. We argue that the ECF for a LHS does not, in fact, solve these problems, but that it is a third, separate position in the relationship between research ethics and clinical ethics. Moreover, we suggest that the ECF for a LHS raises new ethical problems that require additional ethical analysis and justification. Our article contributes to the discussion on the relationship between research ethics and clinical ethics, revealing that although a learning health‐care system may significantly change the landscape of health care, some ethical dilemmas still require resolving on both theoretical and policy‐making levels.